Cost Oriented Autonomous Window Cleaning Robot from Mechatronic Scrap - MechCleanBot. Issue 13 (2021) - Bula, Ines; Bula, Edin; Hajrizi, Edmond
Abstract: The rapid growth of technology meant an increase in the quality of life. As engineers we need to think of new, unique projects by building a robots that will improve the quality and safety of our daily lives. In this paper we present Cost Oriented Autonomous Window Cleaning Robot from Mechatronic Scrap - MechCleanBot, which can be used not only in household but can also be used for skyscraper, offices, various objects, thus cleaning the windows without effort, without getting tired and in many cases without endangering the life of anyone. The moment the robot is placed on the window it will start cleaning the window through the Bluetooth RC Controller application which is taken on the smartphone in advance and through the same application we will be able to control MechCleanBot to clean the window without moving from place at all. All this will be possible through the Bluetooth module HC-06 which is designed for transparent wireless communication which reaches a distance of up to 9 meters. For the realization of this MechCleanBot are used: Arduino Uno R3, Bluetooth HC-06, Gear motors, Motor Shield L298, Neobidium Magnet, Resistor, Servo motor SG9, as well as Transistor IRFZ44N. MechCleanBot is the idea of a compact robot which is able to clean the windows of a house or a building, is quite attractive, so main goal has been the realization of robot which is able to clean windows but also a main goal was to be realized the robot with minimal costs of 16.06 euro, in order to be practical, to reuse e-waste and in same time to recycle, to be easy to use, and to be cost effective.